CLIMATE PERIODS AND PATHOLOGICAL RISKS AMONG FARMERS IN THE COMMUNE OF POBE - SEIDOU, M.; MEDEOU, Fidèle K.; AZONHE, THIERRY HERVÉ S. NICÉPHORE (My University, 2019)
This research is devoted to the study of climatic periods and pathological risks among farmers in the municipality of Pobè. The analysis of Pearson correlation and linear regression tests performed in the XLSTAT software helped to assess the degree of linkage between climatic parameters and malaria, ARI, diarrheal diseases. Main Component Analysis allowed appreciating the appearance of pathological climatic periods. The results obtained show that in the municipality of Pobè during each climatic period, the moments of discomfort are responsible for the direct and indirect pathological risks for farmers. Thus, it is noted direct risks in times of high heat such as headaches (42%), fever (21%), heat pains (21%), vertigo (11%), muscle cramps (11%) and in harmattan period sore throats (45%), dry nostrils (24%), cleft lip (19%) and heels (12%). Indirect risks are the pathological risks of malaria (51%), Acute Respiratory Infections (17%), diarrheal diseases (11%) and intestinal diseases (8%). Faced with these climate-sensitive risks, farmers develop endogenous measures and often resort to traditional medicine, self-medication and before going to a health center.
Keywords: Municipality of Pobè; Health risks; Pathologies; Farmers; Climatic periods